Circulating C-X-C Motif Ligand 13 as a Biomarker for Early Predicting Efficacy of Subcutaneous Immunotherapy in Children With Chronic Allergic Rhinitis - Cheng, Shenghao; Wen, Sihui; Xie, Shaobing; Zhang, Caixia; Zhang, Hua; Gao, Kelei; Fan, Ruohao; Xie, Zhihai; Jiang, Weihong (Frontiers in Pediatrics, 2022)
Background: C-X-C motif ligand 13 (CXCL13) and B cell-activating factor (BAFF) are proven to be involved in inflammatory diseases, but their role in allergic rhinitis (AR) remains unclear. The present study aims to explore the role of serum CXCL13 and BAFF in AR and their clinical values as objective biomarkers to predict the efficacy of subcutaneous immunotherapy (SCIT). Methods: We prospectively recruited 90 children with AR treated with SCIT and collected their serum specimens before SCIT. All patients were followed up for one year and divided into effective and ineffective groups according to their efficacy. The serum levels of CXCL13 and BAFF were detected and compared between two groups. Both cytokines were further evaluated in a validation cohort of 52 responders and 26 non-responders, and their serum CXCL13 and BAFF levels were measured by enzyme linked immunosorbent assay (ELISA). Results: Eighty children completed the follow-up schedule, and 56 children were categorized into the effective group and 24 children into the ineffective group. Serum CXCL13 levels in the effective group were significantly higher than those in the ineffective group (P < 0.05). Receiver operating characteristic (ROC) curves revealed the potential values of CXCL13 as a biomarker in predicting the response of SCIT. Further, in the validation cohort, ELISA results demonstrated that serum CXCL13 levels were increased in responders than non-responders (P < 0.05). ROC curves showed good accuracy of serum CXCL13 in predicting the efficacy of SCIT. Conclusion: Our discover–validation study demonstrated that circulating CXCL13 might serve as a novel biomarker to predict the efficacy of SCIT in children with AR. These results suggested that CXCL13 was involved in the pathological mechanisms of AR and contributed to the underlying therapeutic mechanisms of SCIT.